Impedimental Policies Impacting Shrinking World Solar Industry Eco-Economic Development - Van, Hung Tran; Onyusheva, Irina; Ushakov, Denis; Santhanakrishnan, Radj (International Journal of Energy Economics and Policy, 2018)
This paper is devoted to one of the most current issues in eco-economic development disclosing constraining factors, particularly, the polices impacting shrinking world solar industry. In the research it is underlined the significance of solar industry development as a highly potential green renewable energy resource branch. It is considered the most contemporary sources concerning this issue including European, the US and Asia experts to form the worldwide picture attitude to solar industry and green energy potential. It has been characterized the solar capacity over last 10 years from 2006 to 2016. It has been defined key countries those contributed mostly of total world's solar installed capacity addition for 2016 and have ambitious green energy targets for future. It has been conducted the gap analysis between planned capacities and achievements which is in line with the country's commitment to the IEA in contrast to their achievement in 2017. Moreover, it has been found out policies that are impacting the exponential growth of this industry and what kind of impact these impedimental polices have in context of economic sectoral growth, ecological climate change and other industrial sectors. Keywords: Development, solar industry, green energy, green economy, impedimental policies. JEL Classifications: Q01, Q4, Q5, O1